Simulation of non-structural measures to reduce flooding in Sg. Bentong catchment - Abd Hakim, Nur Wajihah; Salleh, Md Noor; Al-Mamun, Abdullah; Ali, Maisarah; Che Mohd Azmi, Siti Nurain; Ayob, Mohd Fairullazi (IIUM Press, 2024)
Flooding is a frequent and recurring natural disaster in tropical and subtropical regions, often exacerbated by climate change, which may increase both the frequency and severity of such events. Malaysia, due to its geographical location, topography, and climatic conditions, frequently experiences flash and regional flooding, further aggravated by improper development activities. Both structural and non-structural methods have been extensively employed to mitigate flood disasters. Structural measures include dams, levees, floodways, floodwalls, and river improvements. Non-structural measures, however, such as land-use planning and zoning, flood risk mapping, and computer-based flood modeling, are less frequently discussed in the literature. This research focuses on evaluating the effectiveness of non-structural flood prevention interventions in Bentong, Pahang. It investigates proper land-use planning, rainwater harvesting systems, and floodplain management through advanced flood modeling. The study employs HEC-HMS and HEC-RAS models to simulate flood scenarios and generate flood maps. ArcGIS was used to create detailed flood maps, simulating a 100-year, 6-hour storm event over a 99.38 km² area. The results indicated significant water depths ranging from 0.5 to 9.82 meters, highlighting substantial potential for damage. The findings underscore the importance of integrating non-structural measures, such as effective land use planning and rainwater harvesting, into flood disaster management strategies. These measures, combined with detailed flood modeling, offer valuable insights for mitigating the impacts of future flooding events in the study area.